An Arabidopsis jmjC domain protein protects transcribed genes from DNA methylation at CHG sites - Miura, Asuka (Nature Publishing Group, 2009)
Differential cytosine methylation of genes and transposons is important for maintaining integrity of plant genomes. In Arabidopsis, transposons are heavily methylated at both CG and non-CG sites, whereas the non-CG methylation is rarely found in active genes. Our previous genetic analysis suggested that a jmjC domain-containing protein IBM1 (increase in BONSAI methylation 1) prevents ectopic deposition of non-CG methylation, and this process is necessary for normal Arabidopsis development. Here, we directly determined the genomic targets of IBM1 through high-resolution genome-wide analysis of DNA methylation. The ibm1 mutation induced extensive hyper-methylation in thousands of genes. Transposons were unaffected. Notably, long transcribed genes were most severely affected. Methylation of genes is limited to CG sites in wild type, but CHG sites were also methylated in the ibm1 mutant. The ibm1-induced hyper-methylation did not depend on previously characterized components of the RNAi-based DNA methylation machinery. Our results suggest novel transcription-coupled mechanisms to direct genic methylation not only at CG but also at CHG sites. IBM1 prevents the CHG methylation in genes, but not in transposons.